1992
DOI: 10.1136/vr.130.23.505
|View full text |Cite
|
Sign up to set email alerts
|

Slowing the spread of anthelmintic resistant nematodes of sheep and goats in the United Kingdom

Abstract: Anthelmintic resistant nematodes pose an increasing threat to animal welfare and lamb production on lowland sheep farms in the United Kingdom. Based on published information on anthelmintic resistance in nematodes and insecticide resistance in arthropods, seven recommendations are made for reducing the development and spread of anthelmintic resistant nematodes. The two most important are probably to prevent the introduction of resistant worms through the purchase of stock and to reduce the reliance on frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
12

Year Published

1993
1993
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 0 publications
1
59
0
12
Order By: Relevance
“…The use of isolation areas for sick and quarantined to keep the newly acquired or sick animals' aparted from the herd is an important practice in order to prevent the introduction of important diseases and helminth infections, and the likelihood of acquiring resistant parasites would increase proportionately to the amount of newly introduced animals (COLES; ROUSH, 1992). The intensive interregional and interstate transit of goats facilitates the exchange of pathogens and parasites from distant flocks ) and we think that this situation is aggravated by the limited use of quarantine in the dairy and beef flocks.…”
Section: Resultsmentioning
confidence: 99%
“…The use of isolation areas for sick and quarantined to keep the newly acquired or sick animals' aparted from the herd is an important practice in order to prevent the introduction of important diseases and helminth infections, and the likelihood of acquiring resistant parasites would increase proportionately to the amount of newly introduced animals (COLES; ROUSH, 1992). The intensive interregional and interstate transit of goats facilitates the exchange of pathogens and parasites from distant flocks ) and we think that this situation is aggravated by the limited use of quarantine in the dairy and beef flocks.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of the release of new drugs, and given the increasing status of AHR in small ruminants, combinations of drugs with different mechanisms of action began to be used in an effort to delay the development of resistance (SMITH, 1990;COLES & ROUSH, 1992). However, it was found that these combinations could fail, particularly when there was already resistance to one or more drugs, although the use of combinations was found to be valid when inserted in integrated programs of drug resistance management and underpinned by parasitological examinations (LEATHWICK & BESIER, 2014).…”
Section: History Of Ahr In Small Ruminants In Brazil and Around The Wmentioning
confidence: 99%
“…When more than one anthelmintic class is effective, an effort should be made to perform annual (slow) rotation [14]. A single anthelmintic should be used for an entire year, and a second drug used the next.…”
Section: Management Issues and Future Implications Relating To Anthelmentioning
confidence: 99%